UPLC-TOF/MS-based metabolomics reveals the chemical changes and in vitro biological effects in fermentation of white ginseng by four probiotics - Chen, Yincui; Wang, Yunsheng; Zhu, Anqin; Zhang, Liqin; Zhang, Xiang; Zhang, Jin; Zhang, Chuanbo (Frontiers in Microbiology, 2022)
Microbial fermentation is a useful method for improving the biological activity of Chinese herbal medicine. Herein, we revealed the effects of solid-state fermentation by Lactiplantibacillus plantarum, Bacillus licheniformis, Saccharomyces cerevisiae, Eurotium cristatum and multiple strains on total flavonoid content, total phenol content, as well as antioxidants, α-amylase inhibitory activities and α-glucosidase inhibitory activities in white ginseng (WG). Metabolite differences between non-fermented and fermented WG by different probiotics were comprehensively investigated using ultra-performance liquid chromatography time-of-flight mass spectrometry (UPLC-TOF-MS). Results showed that the total flavonoid content, ferric reducing antioxidant power, scavenging activities of DPPH radical and ABTS radical, α-amylase inhibitory activities and α-glucosidase inhibitory activities of WG were considerably enhanced after processing by solid-state fermentation in all strains. The total phenol content was increased by E. cristatum and B. licheniformis fermentation, but decreased by L. plantarum, S. cerevisiae and multi-strain fermentation. Additionally, E. cristatum exhibited stronger biotransformation activity on WG compared to other strains. Significant differential metabolites were mainly annotated as prenol lipids, carboxylic acids and derivatives, flavonoids, polyphenols, coumarins and derivatives. Correlation analysis further showed that changes of these metabolites were closely related to antioxidant and hypoglycemic effects. Our results confirmed that fermentation of WG by different probiotics has distinct effects on biological activities and metabolite composition, and indicating fermentation as an important novel strategy to promote components and bioactivities of WG.